Efficient Computation of the Nonlinear Schrödinger Equation with Time-Dependent Coefficients - Athinoula A. Kosti; Simon Colreavy-Donnelly; Fabio Caraffini; Zacharias A. Anastassi (Mathematics, 2020)
Motivated by the limited work performed on the development of computational techniques for solving the nonlinear Schrödinger equation with time-dependent coefficients, we develop a modified Runge−Kutta pair with improved periodicity and stability characteristics. Additionally, we develop a modified step size control algorithm, which increases the efficiency of our pair and all other pairs included in the numerical experiments. The numerical results on the nonlinear Schrödinger equation with a periodic solution verified the superiority of the new algorithm in terms of efficiency. The new method also presents a good behaviour of the maximum absolute error and the global norm in time, even after a high number of oscillations.